Semiotic Codes in Edgar Allan Poe's Selected Horror Short Stories - Agung Kirana Sembiring (English Teaching and Linguistics Journal (ETLiJ), 2021)
This research is entitled “Semiotic Codes in Edgar Allan Poe’s Selected Horror Short Stories”, a research about semiotic codes by Roland Barthes. This research represents the results of Barthes’ Five Codes in three Edgar Allan Poe’s horror short stories. The main theory used in supporting this research is a theory of semiotic codes as proposed by Roland Barthes (1974). To support this research, the researcher applies a descriptive qualitative method since the data of this research are in forms of words, phrases, clauses, and sentences. The results of this research indicate that there are Barthes’ five codes found in the horror short stories of Edgar Allan Poe, such as: Hermeneutic Code, Proairetic Code, Semantic Code, Symbolic Code, and Cultural Code, in the horror short stories titled, “Berenice”, “The Tell-Tale Heart”, and “The Mask of Red Death”, by Edgar Allan Poe.